2021
DOI: 10.3390/ijerph182413220
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Neighbourhood Variations in the Incidence of Dengue Fever in Jeddah City, Saudi Arabia

Abstract: The rapid growth and development of cities is a contributing factor to the rise and persistence of dengue fever (DF) in many areas around the world. Many studies have examined how neighbourhood environmental conditions contribute to dengue fever and its spread, but have not paid enough attention to links between socio-economic conditions and other factors, including population composition, population density, the presence of migrant groups, and neighbourhood environmental conditions. This study examines DF and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
7
0
1
Order By: Relevance
“…However, release trial results have not yet been reported in hot, low rainfall climates in which Ae. aegypti can occur along with substantial arbovirus transmission [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, release trial results have not yet been reported in hot, low rainfall climates in which Ae. aegypti can occur along with substantial arbovirus transmission [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alkhaldy and Barnett [35] reported that high-density populations and large non-Saudi migrant populations were significantly associated with MBD (p<0.001). Elmardi et al [30] reported that people in urban areas have significantly higher MBDs than in rural (p=0.003).…”
Section: Demographymentioning
confidence: 98%
“…29 Hasil penelitian ini sesuai dengan studi di Sri Lanka yang menunjukkan bahwa kasus demam berdarah tertinggi terjadi di daerah dengan kepadatan penduduk yang tinggi. 33,34 Namun, pengelompokkan kasus DBD karena tingginya kepadatan penduduk masih perlu divalidasi dengan lebih banyak data di masa mendatang karena hal tersebut juga dipengaruhi oleh keberadaan infrastruktur air yang buruk, sehingga memberikan peluang bagi Aedes sp. untuk berkembangbiak.…”
Section: Pembahasanunclassified